1982
DOI: 10.1113/jphysiol.1982.sp014300
|View full text |Cite
|
Sign up to set email alerts
|

Further studies on the mechanism of phosphorylase activation in rabbit liver in response to splanchnic nerve stimulation

Abstract: SUMMARY1. The mechanism of activation of liver phosphorylase after splanchnic nerve stimulation has been investigated in rabbits and compared with the effects of intraportal injections of noradrenaline.2. The increase in the activity of liver phosphorylase-a, the active form of this key glycogenolytic enzyme, in response to injections of noradrenaline was blocked by ,f-adrenergic antagonists, but not by a-adrenergic antagonists, suggesting that the effect of noradrenaline is mediated mainly through f-adrenocep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

1987
1987
1997
1997

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(4 citation statements)
references
References 40 publications
0
4
0
Order By: Relevance
“…Sympathetic innervation of the liver has been proposed to have an important function in the stimulation of hepatic glucose production during exercise on the basis of two premises. First, increases in phosphorylase a activity (9,22) and hepatic glycogenolysis (8,9,14) occur with direct hepatic nerve stimulation. Second, the exercise-induced increase in glucose production is more rapid than changes in arterial glucagon, insulin, and epinephrine levels (7).…”
mentioning
confidence: 99%
“…Sympathetic innervation of the liver has been proposed to have an important function in the stimulation of hepatic glucose production during exercise on the basis of two premises. First, increases in phosphorylase a activity (9,22) and hepatic glycogenolysis (8,9,14) occur with direct hepatic nerve stimulation. Second, the exercise-induced increase in glucose production is more rapid than changes in arterial glucagon, insulin, and epinephrine levels (7).…”
mentioning
confidence: 99%
“…A possible involvement of eicosanoids in nerve action was also indicated by the finding in anaesthetized rabbits in vivo that glycogen phosphorylase activation by preganglionic stimulation of the splanchnic, rather than by postganglionic stimulation of the hepatic nerves, was inhibited by intraperiportal infusion of Indo [34]. Since prostaglandins of the E series were shown to inhibit glucagon-stimulated glycogenolysis and CAMP formation [35,36], the possibility has to be considered that prostaglandins of the F series or thromboxanes may be involved in mediating metabolic nerve action.…”
Section: Comparison Of the Effects Of Nerve Stimulation With Those Ofmentioning
confidence: 96%
“…There is, however, conflicting evidence from rabbits that neither a-nor P-blockers prevent the phosphorylase activation response to nerve stimulation of the liver and conversely that the response to noradrenaline is blocked by a-blockers (Shimazu & Usami, 1982); unfortunately these authors did not measure blood glucose concentrations. Edwards (1972) showed that the effect of splanchnic stimulation on hepatic glycogenolysis was not modified by adrenalectomy and pancreatectomy, thus supporting direct nervous affects on the liver as being important in addition to indirect effects via adrenalin and pancreatic hormones.…”
Section: Nervous Control Of Liver Functionmentioning
confidence: 99%